Mitogen-activated protein kinase-dependent and -independent routes control shedding of transmembrane growth factors through multiple secretases. - Montero, Juan Carlos (2002)
Solubilization of a number of membrane proteins occurs by the action of cell-surface proteases, termed secretases. Recently, the activity of these secretases has been reported to be controlled by the extracellular signal-regulated kinases 1 and 2 (ERK1/ERK2) and the p38 mitogen-activated protein kinase (MAPK) routes. In the present paper, we show that shedding of membrane-anchored growth factors (MAGFs) may also occur through MAPK-independent routes. In Chinese-hamster ovary cells, cleavage induced by protein kinase C (PKC) stimulation was largely insensitive to inhibitors of the ERK1/ERK2 and p38 routes. Other reagents such as sorbitol or UV light stimulated MAGF cleavage independent of PKC. The action of sorbitol on cleavage was only partially prevented by the combined action of inhibitors of the p38 and ERK1/ERK2 routes, indicating that sorbitol can also stimulate shedding by MAPK-dependent and -independent routes. Studies in cells devoid of activity of the secretase tumour necrosis factor-alpha-converting enzyme (TACE) indicated that this protease had an essential role in PKC- and ERK1/ERK2-mediated shedding. However, secretases other than TACE may also cleave MAGFs since sorbitol could still induce shedding in these cells. These observations suggest that cleavage of MAGFs is a complex process in which multiple secretases, activated through different MAPK-dependent and -independent routes, are involved.